Different cerebrospinal fluid drainage methods and chronic hydrocephalus in patients with aneurysmal subarachnoid hemorrhage - Zhou, Yang; Liu, Zhimin; Yan, Huiqin; Peng, Luyao; Chen, Linshuang; Wu, Wanyun; Luo, Wei; Huang, Yongkai; Wu, Botao (Frontiers in Neurology, 2025)
BackgroundChronic hydrocephalus represents a common complication following aneurysmal subarachnoid hemorrhage (aSAH); however, the underlying mechanisms driving its pathogenesis remain incompletely understood. Furthermore, current evidence regarding optimal preventive strategies to mitigate hydrocephalus development remains controversial within the neurosurgical community.ObjectiveTo investigate the efficacy of distinct cerebrospinal fluid (CSF) drainage modalities in mitigating the risk of developing chronic hydrocephalus among patients with aneurysmal subarachnoid hemorrhage (aSAH) through a comparative effectiveness study design.MethodThe patients with aSAH treated in our hospital from January 2021 to January 2024 were analyzed retrospectively. Firstly, the related factors of chronic hydrocephalus in patients with subarachnoid hemorrhage were compared between patients with cerebrospinal fluid drainage and patients without cerebrospinal fluid drainage. Then, the related factors of hydrocephalus in patients with aneurysm subarachnoid hemorrhage with different cerebrospinal fluid drainage were compared. Univariate and multivariate logical regression analysis was used to determine the risk factors associated with chronic hydrocephalus.ResultOf the 246 hospitalized patients with aSAH, whether or not to receive cerebrospinal fluid drainage was associated with the formation of chronic hydrocephalus. A total of 67 patients (27.2%) developed hydrocephalus, of which 47 patients (34.8%) received cerebrospinal fluid drainage, while 20 (18%) patients developed chronic hydrocephalus. Of all IVH patients who received cerebrospinal fluid drainage, 34 (25.2%) received intermittent lumbar puncture drainage, 75 (55.5%) received continuous drainage in the lumbar cistern, and 26 (19.3%) received extraventricular drainage. Univariate analysis showed that different drainage methods had significant differences in postoperative chronic hydrocephalus in patients with aneurysmal subarachnoid hemorrhage (Purge 0.009). Multivariate Logistic regression analysis showed that different ways of cerebrospinal fluid drainage were independent risk factors for chronic hydrocephalus in patients with aneurysmal subarachnoid hemorrhage.ConclusionPatients with aneurysmal subarachnoid hemorrhage must perform cerebrospinal fluid drainage. Among the three different drainage methods: lumbar puncture intermittent drainage, lumbar cistern continuous drainage, and extraventricular drainage, continuous lumbar cistern drainage is more effective in reducing the formation of chronic hydrocephalus.